MultiMedia modeling. 22nd International Conference, MMM 2016, Miami, FL, USA, January 4-6, 2016, Proceedings /: 22nd International Conference, MMM 2016, Miami, FL, USA, January 4-6, 2016, Proceedings. Part I : (2016) - Unknown
No abstract available